Nigella sativa L. Attenuates Oxidative Stress, Inflammation and Apoptosis in Concanavalin A-induced Acute Immunological Liver Damage in Mice - Aqsa Mushtaq; Bilal Aslam; Muhammad Naeem Faisal; Asif Hussain; Sumbul Shamim; Shaneel Kousar; Aneela Gul; Asher Umer (Brazilian Archives of Biology and Technology, 2024)
Abstract Liver’s contribution to innate immunity is eminent. However, uncontrolled inflammatory conditions predispose the liver to immune-mediated injury. Nigella sativa L. is traditionally implicated in infectious, inflammatory, metabolic and hepatorenal complications. This study aimed to evaluate the protective role of N. sativa seed extract (NSE) against concanavalin A (ConA)-induced acute immunological liver injury in mice. In vitro, NSE was subjected to quantitative phytochemical characterization and 1,1-diphenyl-2-picryhydrazyl (DPPH) analysis. In vivo, male Balb/c mice were pretreated with NSE (100, 200 and 400 mg/kg/day, p.o.) and pioglitazone (5 mg/kg/day, p.o.) for seven consecutive days. A single dose of ConA (12 mg/kg, i.v.) was injected and samples were collected for biochemical, histopathological and qRT-PCR analyses after 8 h of ConA injection. In vitro analysis showed considerable quantities of polyphenols and significant DPPH scavenging ability of NSE. In mice, ConA resulted in a significant (p<0.05) increase in liver injury markers (ALT, AST, ALP and TBil) and hepatic oxidative stress (SOD, CAT and MDA). Also, a substantial elevation of pro-inflammatory cytokines (TNF-α, IL-1β and IL-6) in liver tissues was noticed. Furthermore, ConA markedly downregulated PPARγ and upregulated JAK2 and STAT3 expressions. In addition, considerably decreased expressions of Bcl-2 and increased Bax and Caspase-9 were observed. NSE demonstrated hepatoprotective effect in a dose-dependent manner through attenuating liver injury markers, oxidative stress parameters, pro-inflammatory cytokines levels as well as liver inflammation and hepatocyte apoptosis via modulating PPARγ/JAK2/STAT3 and Bcl-2/Bax/Caspase-9 pathways. Conclusively, the antioxidative, anti-inflammatory and anti-apoptotic actions of NSE could protect against acute immunological liver injury.